ArsRS-Dependent Regulation of homB Contributes to Helicobacter pylori Biofilm Formation - Servetas, Stephanie L.; Doster, Ryan S.; Kim, Aeryun; Windham, Ian H.; Cha, Jeong-Heon; Gaddy, Jennifer A.; Merrell, D. Scott (Frontiers in Microbiology, 2018)
One elusive area in the Helicobacter pylori field is an understanding of why some infections result in gastric cancer, yet others persist asymptomatically for the life-span of the individual. Even before the genomic era, the high level of intraspecies diversity of H. pylori was well recognized and became an intriguing area of investigation with respect to disease progression. Of interest in this regard is the unique repertoire of over 60 outer membrane proteins (OMPs), several of which have been associated with disease outcome. Of these OMPs, the association between HomB and disease outcome varies based on the population being studied. While the molecular roles for some of the disease-associated OMPs have been evaluated, little is known about the role that HomB plays in the H. pylori lifecycle. Thus, herein we investigated homB expression, regulation, and contribution to biofilm formation. We found that in H. pylori strain G27, homB was expressed at a relatively low level until stationary phase. Furthermore, homB expression was suppressed at low pH in an ArsRS-dependent manner; mutation of arsRS resulted in increased homB transcript at all tested time-points. ArsRS regulation of homB appeared to be direct as purified ArsR was able to specifically bind to the homB promoter. This regulation, combined with our previous finding that ArsRS mutations lead to enhanced biofilm formation, led us to test the hypothesis that homB contributes to biofilm formation by H. pylori. Indeed, subsequent biofilm analysis using a crystal-violet quantification assay and scanning electron microscopy (SEM) revealed that loss of homB from hyper-biofilm forming strains resulted in reversion to a biofilm phenotype that mimicked wild-type. Furthermore, expression of homB in trans from a promoter that negated ArsRS regulation led to enhanced biofilm formation even in strains in which the chromosomal copy of homB had been deleted. Thus, homB is necessary for hyper-biofilm formation of ArsRS mutant strains and aberrant regulation of this gene is sufficient to induce a hyper-biofilm phenotype. In summary, these data suggest that the ArsRS-dependent regulation of OMPs such as HomB may be one mechanism by which ArsRS dictates biofilm development in a pH responsive manner.